Catalytic oxidative desulfurization of model fuel utilizing functionalized HMS catalysts: characterization, catalytic activity and mechanistic studies. Issue 2 (16th November 2020) - Wang, Fang; Xiao, Ke; Shi, Lin; Bing, Liancheng; Han, Dezhi; Wang, Guangjian
Abstract : In this study, a novel Fe(ii ) porphyrin conjugated amino modified HMS catalyst was synthesized and characterized by BET, XRD, TEM, SEM, and UV-vis techniques. Abstract : In this study, a novel Fe(ii ) porphyrin conjugated amino modified HMS catalyst was synthesized and characterized by BET, XRD, TEM, SEM, and UV-vis techniques. The catalytic oxidative desulfurization performance and the different reaction conditions in model oil were investigated. The results showed that the mentioned FeC4 Pc catalysts which integrated the high surface area of carriers and the high catalytic capacity and accessibility of active components exhibited excellent catalytic activity and reusability. Under the optimized reaction conditions, the desulfurization rate reached 98.4% of model oil enriched with model sulfur compounds. A possible mechanism of the oxidative desulfurization on FeC4 Pc-HMS catalysts was proposed, and our experimental results demonstrated that the catalyst has potential for other oxidative reactions.